Bio-inspired platelet reinforced elastomeric-ceramic composites for impact and high strain rate applications. (10th November 2019) - Crookes, Robert G.; Wu, Houzheng; Martin, Simon J.; Kay, Christopher; Critchlow, Gary W.
Abstract: In this paper we introduce a new elastomeric-ceramic platelet composite inspired by the biological structure of nacre. Composites were manufactured through bulk solvent casting methods with high platelet loadings up to 50% by volume. These platelet-containing composites were specifically engineered and optimised for impact and high strain rate applications where the elastomer undergoes a high degree of non-linear strain rate sensitivity. As such, the mechanical properties of these composites were characterised using dynamic testing methods, namely: dynamic mechanical analysis, and the split Hopkinson pressure bar. It was determined that the composite properties are greatly influenced by the matrix-platelet interface strength, consequently, a coupling agent was used to promote interfacial bonding. The resulting optimised composites showed greatly increased high strain rate compressive strength whilst maintaining high toughness, resulting in a six-fold increase in strain energy over the original elastomer. These elastomeric composites are intended for ballistic impact protection, mainly as an alternative to polyurea strike face coatings on steel.